2 - The Role of Economic Aspiration in Elections in Kenya - Oculi, Okello (Africa Development, 2021)
The violence that erupted, following the 30 December 2007 civic, parliamentary and presidential elections in Kenya is analysed as part of various historical continua anchored on social engineering by colonial officials who sought to control social change after the Mau Mau conflict. Presidents Jomo Kenyatta and Daniel arap Moi built on this colonial strategy for managing challenges by socialist and pro-democracy forces to their hold on power. Moi’s regime had to combat challenges to his electoral fortunes from 1988 onwards and left behind a technology that was a useful investment for 2007/2008 opposition groups. Both forms of social engineering gave prominence to tribalism as an organising tool. The power behind the success of these exercises was economic anxieties rooted in land, widespread unemployment and elite struggles for control of political influence. This perspective allows us to propose that stability in Kenya in the post-conflict period requires a bold counter-social engineering that breaks down efforts to continue the use of tribalism to prevent re-distribution of large landed estates in several parts of the country, particularly Coast and Central Provinces.